STATISTICAL ANALYSIS OF LASER POLARIZATION IMAGES OF BLOOD PLASMA IN DETECTING OF MAMMARY GLANDS PATHOLOGY - N. I. Zabolotna; B. P. Oliinychenko (Medična Informatika ta Inženerìâ, 2012)
There are changes tendentious statistical moments of two-dimensional distribution of azimuth and ellipticity of polarization of a laser image of human blood plasma. Evaluation was carried out under the assumption that small and high level of birefringence  reflects the state plasma "healthy person" and «pathology of mammary glands».